Employability and Employment - Innovative Policies and Measures in the German TVET Cooperation - Henn, Michaela [Verfasser] (My University, 2010)
"Innovations and traditions of German TVET cooperation with developing countries are reflected in the BMZ sector papers and in the practice of Germany's Technical Cooperation. School to work-transition and (youth) employment are topics high on development agendas. [...] Drawing from scientific research and project documentations, this paper highlights those innovations in German TVET cooperation which are explicitly dealing with transition measures. It gives two examples of innovative vocational orientation 'tools' which are facilitating the transition from general compulsory education into TVET in Chile." (Autorenreferat, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; L 5 Beratung & Orientierung; I 2.1 Deutschland; I 2.3.3 Lateinamerika; Internationale Zusammenarbeit; Entwicklungshilfe; Berufsbildung; Berufseinmündung; Zweite Schwelle; Berufsorientierung; Bundesrepublik Deutschland; Chile